2012
DOI: 10.1136/gutjnl-2011-301393
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cells promote colorectal cancer progression through paracrine neuregulin 1/HER3 signalling

Abstract: Paracrine NRG1/HER3 signals initiated by BM-MSC and T-MC promote CRC cell progression, and high tNRG1 expression is associated with poor prognosis in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 53 publications
6
119
3
1
Order By: Relevance
“…Several studies demonstrated anti-tumor effects [8][9][10] whereas others showed tumor promoting effects [11][12][13] of MSCs in different tumor models. Regarding the effects on CRC, most of the studies have shown a pro-cancer effect of MSCs [29][30][31]. Consistently, we observed that trophic factors secreted by MSCs can promote colony formation and growth of a metastasis CRC cell line.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies demonstrated anti-tumor effects [8][9][10] whereas others showed tumor promoting effects [11][12][13] of MSCs in different tumor models. Regarding the effects on CRC, most of the studies have shown a pro-cancer effect of MSCs [29][30][31]. Consistently, we observed that trophic factors secreted by MSCs can promote colony formation and growth of a metastasis CRC cell line.…”
Section: Discussionsupporting
confidence: 71%
“…DeBoeck et al [8] investigated the role of neuregulin-1 (tNRG1) and human epithelial growth factor regulator (HER), and reported that paracrine NRG1/HER3 signals initiated by MSCs promote CRC progression. In the present study, in vitro interactions between MSCs and CCC and potential mediators were further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, our knowledge of colon cancer cell-MSC interactions remains limited, and the role of MSCs within colon tumours has yet to be elucidated. Only one recently published study exists in the literature regarding factors mediating CRC/MSC interactions which revealed that paracrine neuregulin-1/HER3 signals initiated by MSCs promote CRC tumour progression [8]. MSCs are known to secrete a wide range of pro-inflammatory chemokines [9] and are therefore likely to exert a significant effect on surrounding cells.…”
Section: Introductionmentioning
confidence: 99%
“…About 0.25 g of clean fresh tissue was cut into small pieces (1-2 mm 3 ), washed carefully with PBS, and incubated in 1 ml PBS for 1 hour at 37°C in a humidified CO 2 incubator. The samples were centrifuged 26 at 500 g for 10 minutes and 1500 g for 20 minutes. Without any further purification, 4 µl of the final supernatant (i.e.…”
Section: Fluorescent Labelling Of Mvs In Tumour Interstitial Fluidmentioning
confidence: 99%
“…To demonstrate the potential of the microfluidic chip with integrated planar waveguide as a diagnostic tool, fSPT measurements were performed on cell-derived MVs secreted in the interstitial fluid harvested from fresh human breast cancer specimens 26 . To ensure optimal fluorescent labelling of PS-exposing MVs present in the interstitial fluid, again an excess of dye-conjugated Annexin V was added.…”
Section: Size and Concentration Measurements Of Cell-derived Mvsmentioning
confidence: 99%